Nuclear "pasta matter" for different proton fractions - Schuetrumpf, B.; Iida, K.; Maruhn, J. A.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2014)
Nuclear matter under astrophysical conditions is explored with time-dependent and static Hartree-Fock calculations. The focus is in a regime of densities where matter segregates into liquid and gaseous phases unfolding a rich scenario of geometries, often called nuclear pasta shapes (e.g., spaghetti, lasagna). Particularly the appearance of the different phases depending on the proton fraction and the transition to uniform matter are investigated. In this context the neutron background density is of special interest, because it plays a crucial role in the type of pasta shape that is built. The study is performed in two dynamical ranges, once for hot matter and once at temperature zero, to investigate the effect of cooling.
CRIS-Team Scopus Importer:2023-07-24